Investigation of corrosion resistance and impact performance properties of Al2O3/SiC-doped aluminium-based composites - Caligulu, Ugur; Kacmis, M. Vahittin; Karabacak, Abdullah Hasan; Canakci, Aykut; Ozkaya, Serdar (Indian Acad Sciences, 2023)
In this article, the microstructures, mechanical properties, impact strength and corrosion behaviour of AA2024 matrix Al2O3- and SiC-reinforced hybrid composites obtained by using powder metallurgy (T/M) method, which is one of the production methods, were investigated. AA2024/Al2O3-SiC powder mixtures are prepared in different ratios and kept at 560oC for 120 min and then compressed at 500 MPa pressure. In order to determine the microstructure and mechanical properties of the produced samples, microhardness, density, tensile, corrosion and free drop tests were performed with SEM, EDS and XRD images. According to the test results, the best tensile test result of AA2024/Al2O3-SiC hybrid composite materials was determined in hybrid composite materials with 2% reinforcement. The hardness values increased with an increasing reinforcement ratio. As the reinforcement ratio of the materials increases, the corrosion rates decrease, while the corrosion rates increase continuously after the 2% reinforcement ratio. The lowest corrosion rates were determined for hybrid composite materials reinforced with 2% (1.23 mpy). As a result of the drop test, hybrid composite materials with 2% (29.266 kJ m(-1)) reinforcement gave the highest value and drop test values decreased at higher reinforcement ratios.
Keywords: AA2024; Al2O3; SiC; hybrid; corrosion behaviour; impact performance